Exploring Determinants of Early Marriage Among Adolescent Girls in Banama Tingang, Indonesia - Dini, Dini; Budinurdjaja, Pribakti; Nugroho, Adi; Istiqomah, Ermina; Fatimah, Husnul (Heca Sentra Analitika, 2024)
The number of early marriages in Central Kalimantan Province, Indonesia, has increased yearly. According to data from the Indonesian Office of Religious Affairs (KUA) and Office of Population and Civil Registration (Dukcapil), 14,540 couples married early between 2017 and 2021. This problem is caused by several factors, including teenagers' knowledge, parents' education, parents' income, parents' perceptions, and support from parents and peers. This research analyzes factors related to early marriage in Banama Tingang District, Pulang Pisau Regency. This quantitative study used a case-control design conducted in Banama Tingang District, Pulang Pisau Regency, in November 2022. The sample was determined using convenience or accidental sampling methods with 200 teenagers. The results of the Chi-Square analysis showed significant associations between early marriage and parental education (p=0.000) and parental income (p=0.022) but not with adolescent knowledge (p=1.000), parental perception (p=0.173), or parental and peer support (p=0.252). Logistic regression analysis revealed that parental education was the most dominant variable significantly associated with early marriage (p=0.000, Exp B=3.169). There was no significant relationship between adolescent knowledge, parental perception, or support from parents and peers with early marriage among adolescent girls in Banama Tingang District, Pulang Pisau Regency. In conclusion, parental education and income were found to be associated with the incidence of early marriage among young women in Banama Tingang District, Pulang Pisau Regency, with parental education being the most dominant factor.